2012
DOI: 10.1097/qai.0b013e31825ddcfa
|View full text |Cite
|
Sign up to set email alerts
|

Stavudine Concentrations in Women Receiving Postpartum Antiretroviral Treatment and Their Breastfeeding Infants

Abstract: First-line antiretroviral treatment regimens in resource-limited settings used in breastfeeding mothers often include stavudine (d4T). Limited data describing d4T concentrations in breast milk are available. We analyzed d4T concentrations in 52 mother-infant pairs using ultra-performance liquid chromatography-tandem mass spectrometry (lower limit of quantification: 5 ng/ml in plasma, 20 ng/ml in breast milk). Median (interquartile range) d4T concentrations were 86 (36–191) ng/ml in maternal plasma, 151 (48–259… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Another finding in this study was the association of increased GAG2 diversity among infants whose mothers did not have a history of ARV drug use (other than sdNVP for PMTCT). Maternally-administered ARV drugs are known to be transferred to infants in utero and during breastfeeding [39] [41] and can induce ARV drug resistance in infants [42] , [43] . In settings where women are receiving ARV drugs while breastfeeding (e.g., ART for their own infection or a triple drug regimen for prevention of post-natal HIV transmission), this might result in a decrease in the diversity of the infant's virus (i.e., genetic bottlenecking), similar to that observed when children are maintained on non-suppressive ART [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Another finding in this study was the association of increased GAG2 diversity among infants whose mothers did not have a history of ARV drug use (other than sdNVP for PMTCT). Maternally-administered ARV drugs are known to be transferred to infants in utero and during breastfeeding [39] [41] and can induce ARV drug resistance in infants [42] , [43] . In settings where women are receiving ARV drugs while breastfeeding (e.g., ART for their own infection or a triple drug regimen for prevention of post-natal HIV transmission), this might result in a decrease in the diversity of the infant's virus (i.e., genetic bottlenecking), similar to that observed when children are maintained on non-suppressive ART [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Child mortality was still significant and similar to other contemporary cohorts in Malawi [18,19]. The high rate of gastroenteritis associated to early weaning [20,21] has certainly played a role, further supporting the prolonged period of breastfeeding of the new guidelines.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, in our study the only predictor of child mortality was maternal baseline CD4+ count < 350/mm 3 (this was not true for HIV-free survival, due to the significant proportion of transmitting women with high CD4+ count). In a previous study conducted in Malawi in the pre-ART era [19], infant birth weight represented the most important factor associated to mortality up to 2 years. We cannot exclude the role of birth weight in our study since it was of borderline significance in univariate analysis and because this parameter was not available for all the children.…”
Section: Discussionmentioning
confidence: 99%
“…23,32 Two studies have measured tenofovir in BM. In one, tenofovir was measurable in the BM of only 4 out of 25 women sampled and neither study reported corresponding MP or IP concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies report stavudine BM : MP ratios of >1 23 , 31 , 32 with a pooled estimate of 1.21 (1.07–1.36), which is significantly >1; however, infant concentrations approached the lower limit of quantification with a median value of zero. 23 , 32 Two studies have measured tenofovir in BM. In one, tenofovir was measurable in the BM of only 4 out of 25 women sampled and neither study reported corresponding MP or IP concentrations.…”
Section: Resultsmentioning
confidence: 99%